A Educação e a cultura da inclusão da pessoa com deficiência em Breves-PA: o trabalho docente na classe regular do ensino do ensino fundamental - GOMES, Maria do Socorro de Souza (2019)
This research aims to identify and analyze initiatives for inclusion of people with disabilities from actions carried out through the municipality of Breves and in elementary school. From a qualitative point of view, the research adopts a methodological process based on an exploratory field research carried out in the middle of the sphere of activity of the Elementary Education offered by the municipality of Breves in schools, obtaining as main interlocutors the coordination of the HALEFF PINHEIRO center, and teachers of the network. persons with disabilities who are served by schools as well as their families. For data collection, instruments such as questionnaires and recorded interviews were used. The results of the research indicate that the practices undertaken by special education teachers arising from the interaction of society as an instrument of action transformation have been fruitful in strengthening the inclusion of people with disabilities in Breves of the Marajó archipelago.